Quo Vadis Catholic Church? Searching for Identity of a Church with Timorese's faces - Joel Casimiro Costa Pinto (Journal of Asian Orientation in Theology, 2020)
This article presents a panorama of church life in the context of Timor-Leste. In 2015, the Catholic Church in Timor-Leste commemorated 500 years of the evangelization mission. It is within this context that this paper asks: After five centuries of evangelization in Timor-Leste, Quo Vadis Catholic Church? We pose this question to ourselves. This question and the theological reflection arising from it feels heavy to us. The question can also be: Quo Vadimus? As a Church, where are we going? This essay describes the three periods of evangelization in Timor-Leste each having its special and unique characteristics. These characteristics give each period a unique evangelization identity. This article ends by providing some proposals for the future of the Church with Timorese faces.